Factors Affecting Longevity and Reasons for Culling in Dairy Cattle and Buffalo - Akhtar, Hafiz Muhammad Bilal; wadood, Armughan Ahmed; Mehmood, Sarfraz; Aziz, Umar; Andrabi, Syed Murtaza Hassan; Riaz, Muhammad Naeem (Journal of Agriculture and Veterinary Science, 2023)
Dairy cattle and buffalo longevity is critical to economic sustainability and animal welfare in dairy production. This current study embarks on a comprehensive exploration of the multifaceted factors that influence the longevity of these bovine species, subsequently impacting dairy industry profitability and animal selection. This study meticulously dissects the reasons for culling dairy cattle and buffalo, shedding light on the nuanced interplay between genetics, management practices, and emerging technologies. The current analysis delves into the genetic underpinnings of longevity, elucidating the hereditary factors contributing to enhanced lifespan in these valuable dairy animals. Furthermore, it delves into the intricacies of optimal herd management, encompassing nutrition, housing, and healthcare practices, which play a pivotal role in extending the productive lifespan of these animals. Moreover, we examine the dynamic landscape of advancements in biotechnology and genomics, revealing their potential to revolutionize dairy farming by enhancing the longevity and overall productivity of cattle and buffalo. We have amalgamated the latest research findings, presenting a compelling knowledge synthesis understanding the intricate web of factors affecting longevity and culling is paramount as the dairy industry navigates global sustainability and animal welfare challenges. The current study aims to serve as an indispensable resource for scholars, practitioners, and policymakers in the livestock sector, illuminating the path toward a more sustainable and humane dairy sector
Keywords: Animal production; Culling; Dairy animals; Economic Impact; Genetics; Herd management; Longevity; Selective breeding